RETRACTED: Inhibition of Bcl2L12 Attenuates Eosinophilia-Related Inflammation in the Heart - Chen, Xiao; Zhao, Mei-Zhen; Miao, Bei-Ping; Liu, Zhi-Qiang; Yang, Gui; Liu, Jiang-Qi; Yang, Ping-Chang; Song, Jiang-Ping (Frontiers in Immunology, 2020)
Background: The eosinophilic inflammation plays a critical role in myocarditis (Mcd); its underlying mechanism remains to be further elucidated. This study aims to investigate the role of Bcl2-like protein 12 (Bcl2L12) in inducing the defects of apoptosis in eosinophils (Eos) of the heart tissues. Methods: Human explant heart samples were collected. Eosinophilia and myocarditis (Mcd)-like inflammation were induced in the mouse heart by immunizing with murine cardiac α-myosin heavy chain (MyHCα) peptides. Results: Markedly more Eos were observed in heart tissues from patients with Mcd than those from patients with dilated cardiomyopathy. Eos isolated from Mcd hearts showed the signs of apoptosis defects. The Eo counts in the Mcd heart tissues were positively correlated with the Bcl2L12 expression in Eos isolated from the heart tissues. Exposure to interleukin 5 in the culture induced the expression of Bcl2L12 in Eos. Bcl2L12 bound c-Myc, the transcription factor of Fas ligand (FasL), to prevent c-Myc from binding to the FasL promoter, to restrict the FasL gene transcription in Eos. Inhibition of Bcl2L12 prevented the induction of eosinophilia and Mcd-like inflammation in the mouse heart. Conclusions: The Bcl2L12 expression contributes to apoptosis defects in Eos of the Mcd heart. Blocking Bcl2L12 prevents the eosinophilia induction and alleviates Mcd-like inflammation in mice.